1998
DOI: 10.1016/s0194-5998(98)70290-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of Preoperative Lidocaine to Prevent Stridor and Laryngospasm after Tonsillectomy and Adenoidectomy

Abstract: The most important complications from tonsillectomy and adenoidectomy are bleeding, stridor, and laryngospasm. This controlled, double-blind study was designed to investigate the effects of topical and intravenous lidocaine on stridor and laryngospasm. A total of 134 patients scheduled for elective tonsillectomy and/or adenoidectomy were randomly separated into four groups. In the topical lidocaine group 4 mg/kg of 2% lidocaine was applied to subglottic, glottic, and supraglottic areas before endotracheal intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 16 publications
(29 reference statements)
1
26
0
1
Order By: Relevance
“…This result is in agreement with previous studies performed in children anaesthetised with halothane undergoing ear, nose and throat surgery who received intravenous lidocaine in a dose of 1.5 or 2 mg.kg )1 between 1 and 5 min before tracheal extubation [5,6]. In both these studies, laryngospasm or stridor was assessed by clinical observation as a combined outcome and was found to occur in approximately 20% of children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in agreement with previous studies performed in children anaesthetised with halothane undergoing ear, nose and throat surgery who received intravenous lidocaine in a dose of 1.5 or 2 mg.kg )1 between 1 and 5 min before tracheal extubation [5,6]. In both these studies, laryngospasm or stridor was assessed by clinical observation as a combined outcome and was found to occur in approximately 20% of children.…”
Section: Discussionsupporting
confidence: 91%
“…An increased incidence of laryngospasm and apnoea is observed in children compared with adults and complications resulting from hypoxaemia are more common and more severe in children [2][3][4]. Lidocaine has been demonstrated to reduce the incidence of laryngospasm in anaesthetised children [5,6]; however, its effectiveness has been questioned [7,8]. Uncertainty regarding its usefulness is partly explained by the fact that most clinical studies were underpowered to assess the relatively rare event of laryngospasm.…”
mentioning
confidence: 99%
“…A large prospective Scandinavian study found an overall incidence of laryngospasm of 8.7 ⁄ 1000 patients, but it is more common in children, smokers, patients with pre-existing airways infections, and following the use of specific anaesthetic agents [32]. Procedures involving airway manipulation, increased secretions, and blood and surgical debris around the glottic area, particularly during light planes of anaesthesia, are associated with higher risks of laryngospasm [176,177]. The precise pathophysiological mechanism underlying laryngospasm remains unclear, but the end result is a persistent apposition of the vocal cords [25,27,178].…”
Section: Appendix 1: Laryngospasmmentioning
confidence: 99%
“…Suction should be performed under direct vision with the patient deeply anaesthetised, to ensure that the upper airway is clear of any debris; further stimulation should be avoided until the patient is awake [177]. Topical lidocaine sprayed onto the vocal cords at induction has been shown to reduce the risk of laryngospasm following short procedures [182,183].…”
Section: Strategies To Prevent Laryngospasm At Extubationmentioning
confidence: 99%
“…Estos pacientes constituyeron la mayoría de la muestra, especialmente en el grupo en que se usó cuff. El estridor es una complicación reconocida post amigdalectomía 25 y estos resultados lo confirmarían. La proporción de uso de Dexametasona fue mayor en el grupo en que se usó cuff pero su utilización no influyó en la ocurrencia de estridor, en concordancia con lo encontrado en una revisión sistemática de Cochran 26 .…”
Section: Discussionunclassified